Clinical profile of recurrent headache in rural children of Rajasthan: A cross-sectional study - Agrawal, Jagdish Prasad; Rupesh, Masand; Nidhi, Grover (Indian Journal of Child Health, 2018)
Context: Recurrent headache is a commonly encountered clinical entity in rural children. Aims: This study aims to record the clinical profile of recurrent headache in rural children of Rajasthan. Settings and Design: A cross-sectional, observational study in a pediatric outpatient department of a tertiary care teaching hospital. Methods and Materials: A total of 164 children of either sex, between 5 and 17 years of age, presenting with complaints of a recurrent headache were included in the study. All relevant clinical details collected from patients and their relatives were recorded in a structured pro forma. A detailed examination was performed to rule out underlying problems associated with a headache. Headache subtypes were classified according to the International Classification of Headache Disorders, 3rd edition beta, 2013. Pediatric migraine disability assessment test score and Faces pain rating scale were utilized to assess the disability and severity, respectively. Statistical analysis involved summarizing the continuous variables as mean and standard deviation while nominal/categorical variables were expressed as percentages. Results: The mean age was 11.5 years and the M:F ratio was 1:1.1. Adolescents in 13–17 years age group constituted 61.5% (n=101) of the study sample with 58.4% (n=59) female subjects. Primary headaches - tension-type headache (n=77, 46.9%), migraine (n=43, 26.2%), and new daily persistent headache (n=5, 3%) were observed in 125 (76.1%) cases. Common causes of secondary headache were somatization disorder (n=27, 16.5%), ophthalmic problems (n=7, 4.3%), medication overuse (n=3, 1.9%), intracranial tumor (n=1, 0.6), and postictal (n=1, 0.6). Conclusions: Recurrent headache in rural children has distinct etiological profile which mandates a meticulous evaluation for initiating appropriate management.